الاقتصاد الأخضر آلية لتعزيز التنمية المستدامة (تجارب عربية) - دريدي, بشير (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى إبراز دور الاقتصاد الأخضر في تحقيق التنمية المستدامة عن طريق وضع حد للتدهور البيئي من خلال تخفيض المخاطر البيئية وندرة الموارد الإيكولوجية، وتحسين كفاءة استخدام الموارد بخلق الوظائف الخضراء في مختلف القطاعات الاقتصادية، إلى جانب تقليص حجم النفايات وإدارتها بشكل أفضل، وحماية التنوع البيولوجي. وتم استخدام المنهج الوصفي التحليلي والمنهج الاستقرائي لرصد تجارب بعض البلدان العربية للتوجه نحو الاقتصاد الأخضر. توصلت الدراسة إلى أن هناك جهود ومبادرات عربية للتوجه نحو الاقتصاد الأخضر وذلك بتعزيز الطاقات المتجددة والنظيفة، واستدامة نظم النقل، والتحول نحو الصناعات الصديقة للبيئة، والحد من التلوث البيئي، والاقتصاد في المياه واستغلال مياه الصرف الصحي، إلى جانب الاهتمام بالسياحة الإيكولوجية من طرف تونس ومصر، إلا أن هذه المبادرات والمشاريع لا ترقى إلى المستوى المطلوب بالمقارنة مع تجارب أجنبية. Abstract: This study aims to highlight the role of the green economy in achieving sustainable development by putting an end to environmental degradation by reducing environmental risks and the scarcity of ecological resources, improving the efficiency of resource use by creating green jobs in various economic sectors, reducing the volume of waste and managing it better, and protecting diversity. Biological. The descriptive, analytical method and the inductive method were used to monitor the experiences of some Arab countries in moving towards a green economy. The study concluded that there are Arab efforts and initiatives to move towards a green economy by promoting renewable and clean energies, the sustainability of transportation systems, the shift towards environmentally-friendly industries, reducing environmental pollution, saving water, and utilizing wastewater, in addition to paying attention to eco-tourism on the part of Tunisia and Egypt. However, these initiatives and projects are not up to the required level when compared to foreign experiences.
The green economy is a mechanism for sustainable development (Arab experiences)
مقال
Keywords: اقتصاد أخضر ; بيئة ; تنمية مستدامة ; وظائف خضراء ; تلوث بيئي; Green economy ; environment ; sustainable development ; green jobs